2016
DOI: 10.1037/ccp0000097
|View full text |Cite
|
Sign up to set email alerts
|

Brief motivational intervention to reduce alcohol and HIV/sexual risk behavior in emergency department patients: A randomized controlled trial.

Abstract: Objective Given the prevalence of co-occurring risky sexual behavior and drinking among ED patients, we developed a motivational intervention (MI) to address both behaviors. This study tested efficacy of a single session MI compared to Brief Advice (BA) for reducing heavy drinking and condomless sex in adult ED patients screening positive for both. Method 372 patients were randomized to MI (n = 184) or BA (n = 188). Alcohol and sex risk outcomes were assessed over 9-months. Results Generalized Estimating E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 49 publications
3
45
0
Order By: Relevance
“…This study is based on analysis of data from a randomized controlled trial of a brief (one session) MI intervention, compared to a brief advice control (Monti et al, 2016). Patients were not treatment seeking, but were recruited during visits to two Emergency Departments (EDs).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is based on analysis of data from a randomized controlled trial of a brief (one session) MI intervention, compared to a brief advice control (Monti et al, 2016). Patients were not treatment seeking, but were recruited during visits to two Emergency Departments (EDs).…”
Section: Methodsmentioning
confidence: 99%
“…It was also associated with lower odds of reporting condomless sex with a casual partner, and fewer days of sex under the influence of alcohol and/or other drugs (Monti et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…This study demonstrated application of the newly developed Generalized Behavioral Intervention Analysis System (GBIAS) to the coding of sessions of an efficacious MI intervention that reduced both alcohol use and sexual risk behaviors [23]. Using the GBIAS, we reliably coded categories and subcategories of topics on which alcohol- and sex-related conversations focused.…”
Section: Discussionmentioning
confidence: 99%
“…Data were drawn from a randomized clinical trial of an MI intervention targeting both alcohol and sex-risk behaviors, which demonstrated efficacy for reducing both behaviors relative to a brief advice control [23]. The project was approved by hospital and university institutional review boards.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the fact the ED is the primary source of medical care for many patients (Tang, Stein, Hsia, Masalli, & Gonzales, 2010), it presents an opportune setting to intervene on heavy drinking and associated sexual risk taking. Brief motivational intervention (MI) conducted in person with a combined focus on alcohol and sex has been shown to reduce heavy drinking and condomless sex among ED patients (Monti et al, 2016). However, the competing demands placed on staff in ED settings (and health care settings, in general) makes the implementation of in-person MIs logistically challenging (Miller et al, 2006).…”
Section: Introductionmentioning
confidence: 99%